Results of Renal Transplantation on Alloplastic Arterial Grafts - Sagban, Tolga Atilla; Regus, Susanne; Heller, Katharina; Jacobi, Johannes; Apel, Hendrik; Keck, Bastian; Richterstetter, Mario; Eckardt, Kai-Uwe; Wullich, Bernd; Lang, Werner (Urologia Internationalis, 2016)
The aim of this retrospective study was to report results of a consecutive series of kidney transplant patients in whom the renal artery was implanted on a prosthetic vascular graft (PVG).Between January 2011 and December 2014, 208 deceased donor renal transplantations (68 female, 140 male, mean age 52, SD 16 years) were performed. Medical charts and outpatient clinical records of patients who had undergone renal artery implantation on a PVG were reviewed. Extensive literature research added to our 4 patients further 170 published cases during 1989 and 2015 and was compared with regular transplanted patients. Data on patient characteristics, prior vascular procedures, postoperative and long-term outcome were collected.Patients with transplant renal artery anastomosis on a PVG were 4 years older than the control group. Function of the graft was similar in these patients compared to regular renal transplant patients. Resistance indices assessed in our clinic over the entire follow-up period showed also no significant difference between the 2 groups. Thirty-day mortality was 6% (none in our group), which occurred mostly in combination when renal transplantation and PVG replacement was performed simultaneously.Grafting of the renal artery to a PVG is feasible and yields good results, despite the technical difficulties involved.
EVALuna2:3839